گەشەپێدانى سیاسیى لە کوردستاندا - حەمەد, دلێر ئەحمەد (Sulaimani Journal for Humanities, 2003)
Process of political development in Kurdistan, is an important subject in political field and sociology of Kurdish nation. Until nowadays, the scientists and researchers did not make any subjective and scientific research about that subject. The developed American and west Euroupe universities especially colleges and departments, institute and academic centers have been for along time mentioned the importance of political development in the Third World Countries. But unfortunately Kurdistan universties ignored this field and did not mention the subject basically. For writing this subject we took benefit from several scientific sources especially those who made political development theories e.g ,Robert Dal , Hentigton ,Iston, Almond,… Etc. The research contain these subjects :- 1-General characteristics of the research . 2- Political development trends. 3- Socio — political structure of Kurdish people . 4- Political development tools. 5- Democratical and political pluralism. 6- Obstacles of political development . 7- The role of eliied kurdish politicians . After analysing and studying these sectors , the researcher shows the most important results.